Pengembangan Karakter Rasa Keadilan Berbasis Permainan Tradisional Untuk Anak Usia 7-9 Tahun - Mariska Santi; Gregorius Ari Nugrahanta (Jurnal Holistika, 2023)
Parents have expressed concern over the recent crisis in children's sense of justice. Various efforts have been made to overcome this problem, one of which is character development from an early age. This study aims to develop a guidebook based on traditional games to foster a sense of justice in children aged 7-9 years. For this purpose, the Research and Development (R&D) ADDIE type research methodology was employed. This study involved ten teachers for the purposes of needs analysis, ten validators with expertise from various related fields, and eight children as subjects in a limited trial. The study's findings show that: 1) the traditional game-based justice character education guidebook for children aged 7-9 years is appropriate and developed based on the ADDIE stages, 2) through expert judgment carried out by the validator, the guidebook obtains an average score of 3.77 with the qualification "very good" and the recommendation "no need for revision," and 3) the implementation of the guidebook influences the development of the character of justice. The final self-assessment's mean score (M = 3.7875, SE = 0.8332) is higher than the initial self-assessment's mean (M = 1.8750, SE = 0.6748). This variation shows value of t (7) = 13.844, p = 0.000 (p 0.05). With the influence of 96.48% and the level of effectiveness according to the N-Gain Score test of 89.25%, the size of the effect falls into the "big effect" and the "high" category, respectively. Based on the results of this study, it can be concluded that the guidebook based on traditional games is effective in cultivating the character of a sense of justice in children aged 7-9 years.